Formation of Economically Sound Tax Consequences on Purchase and Sale of Foreign Goods (Case Study on Customs Procedure of Customs Warehouse) - E. Yu. Sidorova (Финансы: теория и практика, 2020)
The aim of the article is to develop a typology for purchase and sale of foreign goods under the customs procedure of the customs warehouse and to propose a mechanism for the formation of economically sound tax consequences of VAT based on this typology. The subject of the research is transactions with goods under the customs procedure of the customs warehouse and their taxation mechanism. The methodological basis was economic methods, a generalization method, and a comparison method to study the approaches in Russia and abroad to the formation of the institutional structure of the customs procedure of the customs warehouse. The study results are a typology of purchase and sale of foreign goods under the customs procedure of the customs warehouse, the base for economically sound tax consequences that comply with the principle of neutrality in determining the tax consequences of VAT. The author concludes that for taxpayers relied on economic rather than tax interests, it is necessary to create conditions in the tax and customs legislation of the Russian Federation that taxation was identical in identical operations. Thus, it is necessary to clarify the norms of Article 147 of the Tax Code of Russia, so that under the current regulation were no legal opportunities to reject Russian territory as a place of sale of goods located in the Russian customs warehouse when they undergo the customs procedure of the customs warehouse. The directions for future research are to develop a mechanism for introducing economically sound tax consequences that comply with the principle of neutrality in determining VAT for sale of foreign goods imported into the territory of the Russian Federation and placed under the customs procedure of the customs warehouse.